El retorno de Moscú: la gran estrategia de Rusia en la era Putin (2000-2020) - Gonzalez Levaggi, Ariel (El Colegio de México A.C., 2020)
Since Vladimir Putin’s ascent to power, Russia has combined political and economic stability with a greater assertiveness on the global stage, which has laid the groundwork for Moscow’s return to the forefront of international politics. The paper presents the principal discussions around the grand strategy of the Russian Federation and analyzes the trajectory of its foreign policy from the arrival of Vladimir Putin to power to the beginning of the global covid-19 crisis. From the perspective of neoclassical realism, the principal argument is that Russia is implementing a pragmatic strategy based on a trio of objectives: preservation of its status as a global power, maintaining its hegemonic role in the post-Soviet realm, and preventing the expansion of nato. These are implemented using a wide range of tools, including military coercion. The paper then addresses the evolution of Russia’s pragmatic international strategy, which has led to a series of tensions with the West following the crisis in Georgia in 2008 and in Ukraine in 2014, in parallel with the ascent of an alternative Euro-Asian vector.